PENERAPAN METODE FUZZY TIME SERIES CHEN DALAM SISTEM PERAMALAN PRODUKSI UNTUK OPTIMALISASI PENGADAAN BAHAN BAKU PADA PERUSAHAAN MANUFAKTUR - Sasha Alicia; Lena Magdalena; Ridho Taufiq Subagio (Universitas Methodist Indonesia, 2025)
Fluctuating and dynamic production demands require manufacturing companies to adopt adaptive, data-driven planning systems. However, in manufacturing companies producing plastic ropes such as twine, nets, and yarn, production planning is still conducted manually without a systematic quantitative approach. This study aims to design a production forecasting system using the Fuzzy Time Series Chen method, which can address uncertainty in time series data. Monthly production data from January 2022 to December 2024 were used for testing. The results show that this method provides good forecasting accuracy, with MAPE values of 30.15% for twine, 17.89% for nets, and 16.91% for yarn. The production estimates for January 2025 are 70,162 units (twine), 50,599 units (nets), and 81,315 units (yarn). These findings indicate that the FTS Chen method can improve efficiency and accuracy in production planning.